Class Actions and Limited Vision: Opportunities for Improvement Through a More Functional Approach to Class Treatment of Disputes - Jeffrey W. Stempel (Washington University Law Quarterly, 2005)
Part I of this Article describes the evolution of the perception of the modern class action from populist darling to greedy lawyer pariah, including recent passage of CAFA. Part II examines the degree to which different types of cases present different potential benefits and detriments of class action treatment and explains why investor class actions, including those brought by institutional investors, are particularly likely to benefit from class treatment, are resistant to many of the perceived problems of class actions in other contexts, and should receive a warmer welcome from courts, both in absolute terms and relative to other types of class actions. Part III discusses the continuing underutilization of the class action and the degree to which potential benefits of class treatment are lost due to an excessively formal application of Rule 23. Two significant problem areas are examined, including refusal to use partial class treatment in mass tort matters and reluctance to accord class treatment to Rule 10b-5 damages claims. In addition, the Supreme Court’s recent decision in Dura Pharmaceuticals, Inc. v. Broudo is discussed, as it represents an example of an overly grudging judicial approach to investor class actions (even though it is technically a case interpreting the loss causation and particularized pleading requirements of the PSLRA and not a class action opinion per se). Part IV outlines and defends a flexible approach to class treatment that can be applied in a case-specific fashion to enable more effective use of class actions for vindicating civil wrongs as well as protecting non-culpable defendants.
Keywords: Class actions (Civil procedure); Securities; Shareholder lawsuits; Class Action Fairness Act of 2005; Federal Rules of Civil Procedure; United States